THE UTILIZATION OF ENDE BEACH TOURISM OBJECTS AS A LEARNING RESOURCE IN IMPROVING ENGLISH LANGUAGE SKILLS AT ENGLISH LOVER COMMUNITY (ELC) ENDE - Pali, Agustina; Sadipun, Berty (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
A positive natural environment can have positive implications for improving one's English language skills. The analysis of the situation faced by the partners was the minimum mastery of English basic skills, which resulted in a very low level of confidence in using English. This Community Service activity aims to improve the English skills of activity partners who are members of the English Lover Community (ELC) Ende through the use of Ende Beach tourism objects as a source of learning inspiration. The method of community service activities is to carry out mentoring through several stages of organizing and mentoring techniques including interviews, pre-tests, interactive lectures, questions and answers, contextual learning, discussions, drilling, demonstrations and post-tests. This activity had a positive impact on improving the English language skills of Ende's English Lover Community (ELC) participants. English proficiency in this case is an increase in vocabulary and pronunciation mastery of Ende's English Lover Community (ELC) participants both in quantity and quality. In addition, it also has positive implications for the ability to compose learned vocabulary into English sentences and re-express sentences that have been strung into good and correct English pronunciation, as well as an increase in the ability to compose English sentences into short paragraphs and the ability to read these compiled paragraphs with correct English pronunciation and intonation. The improvement in these skills can be seen from the increasing in the average score of pre-test (60.33%) to post-test (81.33%)